Volterra series expansion for state quadratic systems - Jelali, Mohieddine; Schwarz, Helmut (Zielona Góra: Uniwersytet Zielonogórski)
A review of two methods to compute the kernels of a Volterra series expansion via flow and by the Carleman bilinearization for non-linear analytic systems with linear control is presented. We give explicit formulae especially for state quadratic systems. Furthermore, illustrative examples are given, and the two methods are briefly compared.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka